Field performace of coffee progenies and cultivars with specific resistance to rust - Costa, Joyce Cristina; Carvalho, Carlos Henrique Siqueira; Matiello, José Braz; Almeida, Saulo Roque; Carvalho, Samuel Pereira; Baliza, Danielle Pereira (Coffee Science - ISSN 1984-3909, 2013)
The aim of this research was to evaluate the yield and other agronomic characteristics of coffee progenies with specific resistance to rust. An experiment was carried out at the Experimental Farm of MAPA/Fundação Procafé (MAPA/ProCoffee Foundation) in Varginha, MG, Brazil. The experiment was set up in January 2003 in a randomized complete block design with 12 progenies and two cultivars, five replicates and four plants per plot. The characteristics of average yield, maturation stage and screen analysis were asssessed. The data were subjected to analysis of variance and when there were significant effects from treatments, the means were compared by the Scott-Knott test. For the purpose of facilitating indirect selection, we sought to investigate the degree of association of the characteristics under study by means of the estimates of phenotypic correlation among the characteristics evaluated. Subsequently, genetic distances were estimated by the generalized Mahalanobis distance method to verify the variability among progenies. The results obtained allow us to verify the existence of variation among progenies and cultivars when the characteristics are evaluated separately. It is not recommended to apply indirect selection on the characteristics assessed because the average yield of coffee grains is not strongly associated with the other characteristics. The progenies Arara planta 418 and Catucaí Amarelo 20/15 are recommended for future crosses, considering that these genetic materials are more productive than the control Catuaí Amarelo IAC 66/69 and have genetic divergence. This information may help breeding programs for specific purposes upon enabling the appropriate choice of parents.